A study on failure of lift system at low-cost high-rise building / Muhamad Saufi Akmal Che Rosslim - Che Rosslim, Muhamad Saufi Akmal (Faculty of Architecture, Planning and Surveying, 2012)
Lift system is very important at present because it is one of transport used in the highrise building. It aims not only to consumers but it is also used as transporting goods. Operation performed on a lift will help smooth transport and can save time when compared with the use of stairs. For low-cost apartment lift system one of the aspects that are important to facilitate the movement of residents in the building. Now days in Malaysia, we are used to hear a lot of problems about the service lift at low cost flats. Improve the quality of life, human behaviour, lack of responsibility among users especially vandalism is a problem that is always in the state on the news and articles. That are the problem must be faced by the building management in providing convenient service to user. Dewan Bandaraya Kuala Lumpur ( DBKL ) is one of the local authority which manage their public housing by themselves. At DBKL there has department which manages the affairs of maintenance of buildings owned. Literature review on lift system is the first step to carry out the research, followed by observation and interviews. There are four case studies that have been selected for observations and interviews. Through this can identify the cause of the lift failure at low cost flats. Therefore, interviews were carried out with the DBKL maintenance department staff and by distributing questionnaires to users which are residents of the building. From the data analyze and the result of interviews, it show the main cause of lift system failure at low cost apartment is vandalism which is the attitude of users.